Enablers and barriers to implementing an interdisciplinary experiential learning program for university students in a Canadian rehabilitation centre - Eggiman-Ketter, Jordan; Derrough, Benjamin; Wolfe, Dalton L.; Unger, Janelle (Frontiers in Rehabilitation Sciences, 2024)
Objective: This qualitative study aims to identify a comprehensive set of enablers and barriers to implementing an interdisciplinary experiential learning program for university students at a Canadian rehabilitation centre. Methods: A researcher conducted one-on-one semi-structured interviews with individuals from four key stakeholder groups (i.e., rehabilitation centre leadership, clinicians, university clinical coordinators, and health and rehabilitation students). Interviews and data analysis followed the Theoretical Domains Framework (TDF) which is designed to identify possible cognitive, affective, social, and environmental influences on program implementation. Interviews were transcribed verbatim, and two researchers coded data independently to identify major themes of enablers and barriers to implementing an interdisciplinary experiential learning approach to rehabilitation care. Results: From a total of 12 interviews, domains of the TDF were identified to represent overarching themes which were (1) enablers (i.e., reinforcement, beliefs and consequences, optimism, professional identity, knowledge, and skills), (2) barriers (i.e., environment/resources and beliefs and capabilities), and (3) program development (i.e., goals and evaluation which was not previously a TDF domain). A list of recommendations to implementing an interdisciplinary experiential learning program was created that represented qualitative data from each stakeholder group.This study provides insight on the potential enablers and barriers for developing an interdisciplinary experiential learning program for university students within rehabilitation centres. This type of program could enhance educational curriculums, student and clinical experiences, and patient outcomes. Findings inform recommendations for developing an interdisciplinary program in teaching hospitals and explore the potential impact. Future research and pilot studies will need to be conducted to fully understand the effects of implementing an interdisciplinary experiential learning approach within rehabilitation centres.